2019
DOI: 10.1097/cm9.0000000000000204
|View full text |Cite
|
Sign up to set email alerts
|

Regular transient limb ischemia prevents atherosclerosis progression in hypercholesterolemic rabbits

Abstract: Background: Endothelial dysfunction, the initial pathogenic factor in atherosclerosis, can be alleviated via transient limb ischemia. We observed the effects of regular transient limb ischemia (RTLI) on atherosclerosis in hypercholesterolemic rabbits. Methods: Twenty-eight rabbits were randomized to control, cholesterol, sham, ischemia groups ( n = 7 each) between October 2010 and March 2011. They were fed a normal diet in the control group an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Similarly, it has recently been reported that the incidence rate of ASO rose with increasing age, particularly in people aged >70 years old [11]. It has been confirmed that interventional therapy was significantly superior to conservative therapy in terms of clinical effect and prognosis [12]. Smoking increases the incidence rate of vascular restenosis, so the risks of severe lower limb ischemia and amputation rise.…”
Section: Discussionmentioning
confidence: 79%
“…Similarly, it has recently been reported that the incidence rate of ASO rose with increasing age, particularly in people aged >70 years old [11]. It has been confirmed that interventional therapy was significantly superior to conservative therapy in terms of clinical effect and prognosis [12]. Smoking increases the incidence rate of vascular restenosis, so the risks of severe lower limb ischemia and amputation rise.…”
Section: Discussionmentioning
confidence: 79%
“…Although the high sensitivity of the HR-VWI-based molecular image method permits the detection of subtle morphological and physiological changes of AS plaque with small sample sizes, this animal experiment still suffers from several limitations including essential differences in disease progression from humans, lack of external validation for clinical management, and long duration to assess disease progression. [28][29][30] Here, the concept of triangulation by image-evaluating, histology validation, and statistical analysis were applied to increase confidence that an objective exact method was correctly conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also provided preliminary evidence of the mechanism underlying the preventive effect of RTLI on atherosclerosis, which we had detected in our previous study. 25 Various pharmacological interventions improve EDV, including the use of antioxidant vitamins and endothelial nitric oxide synthase (eNOS) cofactor tetrahydrobiopterin (BH4). [35][36][37] Endothelial function can also be improved by lifestyle changes, including physical exercise and weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22][23][24] In a previous study, we demonstrated that regular transient limb ischemia (RTLI), induced by six cycles of 5-min ischemia and 5-min reperfusion of the hind limb, implemented daily for 12 weeks could prevent atherosclerosis in hypercholesterolemic rabbits. 25 However, the mechanism by which RTLI protects against atherosclerosis remains unknown. We hypothesized that RTLI could protect endothelial function against the damage induced by hypercholesterolemia.…”
Section: Introductionmentioning
confidence: 99%